IMPLEMENTASI KEWENANGAN BAWASLU PADA PENGAWASAN PEMUTAKHIRAN DAFTAR PEMILIH DALAM DAFTAR PEMILIH BERKELANJUTAN - Hazamuddin; La Ode Bariun; La Ode Munawir (Halu Oleo University, 2023)
The purpose of this study is to determine the implementation of Bawaslu's authority in supervising the updating of voter lists in the continuous voter list. The research method used in this study is normative legal research, namely research by studying laws, theories and concepts related to the problem under study by examining available literature. The results of the study show that based on the recommendation of Law Number 7 of 2017 it has regulated the provisions of the Bawaslu's obligation to oversee the process of updating and maintaining voter data on an ongoing basis for the KPU's task of updating voter data on an ongoing basis. However, in terms of regulations, KPU, especially Regency/Municipal KPU, is only limited to providing a copy of PDPB recapitulation to Regency/City Bawaslu, not accompanied by updated data by name by address, so in total the role of updating and maintaining sustainable voter data is only monopolized by the KPU and not there is an opportunity for Bawaslu to fulfill the oversight obligations set out in the law. The process of implementing continuous voter data updating by the KPU of North Buton Regency is carried out in private, the North Buton Regency Bawaslu is only given the Minutes of Recapitulation every month. If access to that data does not exist or is limited, then suggestions and improvements to the voter list by the Election Supervisor will be even lower, and may even be of no value.